2020
DOI: 10.1038/s41419-020-03027-2
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPase RAB6 deficiency promotes alveolar progenitor cell renewal and attenuates PM2.5-induced lung injury and fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease characterized by chronic non-specific inflammation of the interstitial lung and extensive deposition of collagen fibers leading to destruction of lung function. Studies have demonstrated that exposure to fine particulate matter (PM2.5) increases the risk of IPF. In order to recover from PM2.5-induced lung injury, alveolar epithelial cells need to be repaired and regenerated to maintain lung function. Type 2 alveolar epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…39 AS-IV is widely used to prevent respiratory diseases, but its protective effect on PM2.5-induced lung injury is rarely reported. Although many advances have been made in understanding the molecular mechanisms of PM2.5-induced lung injury, [40][41][42] there is still a lack of preventive and therapeutic strategies. In our study, we found that AS-IV significantly ameliorated pulmonary edema in rats with PM2.5-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…39 AS-IV is widely used to prevent respiratory diseases, but its protective effect on PM2.5-induced lung injury is rarely reported. Although many advances have been made in understanding the molecular mechanisms of PM2.5-induced lung injury, [40][41][42] there is still a lack of preventive and therapeutic strategies. In our study, we found that AS-IV significantly ameliorated pulmonary edema in rats with PM2.5-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“… 77 , 84 , 85 In PM2.5-induced lung injury, knockout of RAB6 activates the Wnt/β-catenin signalling pathway by inhibiting the secretion of DKK1, thus promoting the self-renewal of type II alveolar epithelial cells (AEC2) during lung repair. 86 Folliculin (FLCN) deletion in pulmonary mesenchymal cells is the leading cause of cystic lesions in Birt-Hogg-Dubé (BhD) syndrome. A significant decrease in the activity of the Wnt/β-catenin signalling pathway was detected in lung tissues with FLCN knockout, indicating that inhibition of the Wnt signalling pathway is related to the abnormal development of alveoli.…”
Section: Function Of the Wnt/β-catenin Pathway In Diseasesmentioning
confidence: 99%
“…Fibrosis can a significant pathological state in many organs, such as heart ( Gao et al, 2012 ; Liu et al, 2017 ; Ge Z. D. et al, 2019 ), lung ( Yang et al, 2020 ), kidney and liver, and may result in the distortions of organ structure and organ dysfunction ( Li et al, 2016 ; Warisara et al, 2020 ). Pro-fibrotic mediator TGF-β ( Guo et al, 2010 ) and its signaling pathways play an important role in the process of epithelial-mesenchymal transition and tissue fibrosis ( Li et al, 2016 ; Warisara et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%